The Analysis of Information Content towards Greenhouse Gas Emissions Disclosure In Indonesia’s Companies - Siska Pradini, Harlinda; Kiswara, Endang (Diponegoro Journal of Accounting, 2013)
This study aimed to obtain empirical evidence about the influence of ISO 14001 certifiedEnvironmental Management System, the existence of environment function, report environmentinformation in accordance with the Global Reporting Initiative version 3.1, the rank of PROPER,firm size, companies’ leverage, companies’ profitability and type of industry to the extent ofgreenhouse gas emissions disclosure in Indonesia companies. The population of this study was allof companies listed in Indonesia Stock Exchange (ISX) in 2010 and 2011. Sample consists ofcompanies in agriculture, mining and manufacture sectors that disclosed their greenhouse gasemissions. The total sample was 30 companies, with observation’s period is two years so the totalsample which be checked was 53 reports. Data analysis was performed with the classicalassumption and hypothesis testing that it used regression analysis. The results of this studyindicated that the factor of report environment information in accordance with the GlobalReporting Initiative version 3.1, the rank of PROPER and firm size had significantly influence tothe disclosure of greenhouse gas emissions. Meanwhile, ISO 14001 certified EnvironmentalManagement System, existence of environment function, companies’ leverage, companies’profitability and type of industry had no significant effect on the disclosure of greenhouse gasemissions in Indonesia. Implication of this research showed that practice of greenhouse gasemissions disclosure was still minimize to fulfil ISO 14064-1 guideline.